Complex skull base brain tumor resection: the role of microvascular doppler in surgical precision and outcomes - Shen, Kecheng; Sun, Liang; Zhai, Weiwei; Kong, Lijuan; Zhu, Jiandong; Yu, Zhengquan; Wu, Jiang (Frontiers in Oncology, 2025)
ObjectiveTo investigate the role of Doppler microvascular ultrasound (MVD) in skull base surgery for the intraoperative assessment and protection of arterial blood flow.MethodsThe clinical data of 56 patients who underwent surgery at the Department of Neurosurgery, First Affiliated Hospital of Soochow University between September 2017 and June 2024 were retrospectively analyzed. All patients underwent skull base tumor resection assisted by intraoperative microvascular Doppler (MVD). The procedures involved complex skull base tumors, including lesions in the sellar region, sphenoid ridge, and cavernous sinus. During surgery, MVD was utilized to monitor blood flow in vessels adjacent to the tumors. The spatial relationship and patency of the vessels and tumors were evaluated in conjunction with preoperative multimodal imaging.ResultsNo intraoperative vascular injuries were observed among the 56 patients, confirmed by intraoperative Doppler monitoring and postoperative imaging. All patients had favorable postoperative outcomes, including no new neurological deficits. MVD facilitated precise intraoperative localization and evaluation of blood vessels, which was quantitatively supported by significant increases in contrast-to-noise ratio (CNR) after Doppler application. In two representative cases, the addition of FLOW800 fluorescence imaging provided further CNR improvement, suggesting enhanced visualization and vascular protection. Details of the CNR quantification process are provided in the Methods section.ConclusionMVD provides real-time intraoperative information on arterial blood flow during skull base surgeries, enabling surgeons to identify and preserve critical vessels, thereby improving surgical safety, resection accuracy, and patient outcomes. With ongoing technological advancements, the integration of MVD and fluorescence imaging is expected to play an increasingly vital role in complex skull base procedures.